SUSTAINING THE MALAYSIAN MONARCHY’S HERITAGE: HOW SHOULD IT BE POSITIONED TO INTERNATIONAL TOURISTS? (Journal of Event, Tourism and Hospitality Studies, 2024)
Tourism industry relies heavily on good marketing strategy, which becomes imperative for destination marketers to focus on when building long-term consumer engagement, loyalty, and relationships by adopting a sustainable marketing strategy and ultimately safeguard heritage sustainability. This study selects the Malaysian monarchy’s heritage as the research subject and positions strategy as a method to segment and profile international tourists to the said heritage. Respondents were surveyed in July and August 2022, at a museum in Malaysia. Using the Ward method, the clustering analysis identified three clusters, i.e., ‘the royal enthusiast’, ‘the apathetic tourists’, and ‘the inclined royalist’. The main benefits sought by respondents were ‘accessibility’, ‘quality of facilities’, and ‘an increase of knowledge’. Respondents viewed that there should be a focus on ‘representation of the monarchy’s heritage to the Malaysian people and identity’, highlighting that it is ‘a country with nine royal states’, and is therefore unique. Since positioning is about the intention to highlight strengths and distinctiveness in the marketplace, the Malaysian monarchy’s heritage should therefore be positioned in the minds of international tourists as ‘a rich heritage destination with nine royal states’, which is uniquely Malaysia.  The clustering of tourists may enhance the consumption intention and achieve continuous sustainable strategic orientation in preserving the Malaysian monarchy’s heritage.